PROSTHODONTIC REHABILITATION OF MAXILLOFACIAL DEFECT WITH MAGNETICALLY RETAINED MAXILLARY OBTURATOR - Muhammad Bilal; Faryal Saeed Abdal; Mian Farrukh Imran et al. (Journal of University Medical & Dental College, 2018)
ABSTRACT:This case report deals with a rehabilitation of a patient with an extensive maxillary defect using a two-piece intra oral prosthesis obturating the defect. Retention of ﬁrst piece was achieved by snug ﬁt of the prosthesis to underlying tissue and adjacent teeth whereas the second piece was retained with the help of magnets. The rehabilitation procedure resulted in improved function, aesthetics, comfort and conﬁdence to the patient thus enabling him to have improved quality of life. This case report brieﬂy describes the quick and simple lab method of positioning the retention magnets in maxillary obturator, in the rehabilitation of deformed patients.